Alternative Method for Full Oral Rehabilitation in Patients with Pycnodysostosis Syndrome: A Case Report - Costa MM; Pennisi PRC; Oliveira ACZM; Oliveira JEC; Oliveira GV; Moffa EB; Paranhos LR (Dove Medical Press, 2020)
Márcio Magno Costa,1 Pedro Rogério Camargos Pennisi,1 Andréa Cristina Zacarias Martins de Oliveira,2 João Edson Carmo de Oliveira,1 Gustavo Vilela Oliveira,3 Eduardo Buozi Moffa,4 Luiz Renato Paranhos1 1Federal University of Uberlândia, School of Dentistry, Uberlândia, MG, Brazil; 2Private Clinic, Uberlândia, Brazil; 3Federal University of Uberlândia, School of Mechanical Engineering, Uberlândia, MG, Brazil; 4University Center - UNIFAE, School of Dentistry, São João da Boa Vista, SP, BrazilCorrespondence: Luiz Renato ParanhosFederal University of Uberlândia, Uberlândia, MG, BrazilTel +55 34 32258145Email paranhos.lrp@gmail.comAbstract: Pycnodysostosis (PYCD) is a rare autosomal recessive skeletal dysplasia arising from a change in the production of the cathepsin K enzyme and it is also known as Maroteaux-Lamy Syndrome. The main changes in the buccal and maxillofacial region are modifications of the facial bones (leading to the loss of the mandibular angle due to micrognathia), deep palate, premature and/or delayed tooth eruption, hypopneumatization of the maxillary sinuses, chin hypoplasia, hypercementosis, enamel hypoplasia, hyperdontia, incomplete dentin calcification, root hypoplasia, pulp chamber obliteration, and increased free functional space. This paper aims to report a case of a patient with PYCD, in which are highlighted the oral manifestations of this syndrome and present an option of oral rehabilitative treatment through a removable overdenture made on natural tooth of the patient. The technique of dental coating through overdenture is a simple, viable and conservative alternative for oral rehabilitation of patients with large maxillomandibular discrepancies, as in cases of pycnodysostosis, especially in the presence of increased free space – characteristic of patients with this syndrome. The result was quite satisfactory both aesthetically and functionally and provided a better life quality for the patient.Keywords: malocclusion, pycnodysostosis, oral rehabilitation